2021
DOI: 10.1007/s11205-021-02626-6
|View full text |Cite
|
Sign up to set email alerts
|

What Does Really Drive Consumer Confidence?

Abstract: We construct a novel index of households' macroeconomic environment (HOME) based on the data from 22 high-income European countries between 2002 Q1 and 2018 Q4. The resulting index is in line with the broad features of the countries' business and financial cycles and captures well households' perception of their underlying economic situation. We discuss joint properties of the HOME index and the widely employed survey-based consumer confidence indicator. We show that households' expectations are tightly linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…It concluded that confidence in the financial situation of the household itself is more important than confidence in the economic situation in general in determining household savings decisions, with that impact having increased substantially after the 2007-2008 financial crisis. This result agrees with the main findings in Malovaná et al (2021) about the decisions of households to take on credit, based upon their expectations. See also Ganong and Noel (2019) for an analysis of spending after the exhaustion of unemployment subsidies, which may occur during or after the occurrence of a severe economic crises, such as the current one.…”
Section: Literature Reviewsupporting
confidence: 92%
“…It concluded that confidence in the financial situation of the household itself is more important than confidence in the economic situation in general in determining household savings decisions, with that impact having increased substantially after the 2007-2008 financial crisis. This result agrees with the main findings in Malovaná et al (2021) about the decisions of households to take on credit, based upon their expectations. See also Ganong and Noel (2019) for an analysis of spending after the exhaustion of unemployment subsidies, which may occur during or after the occurrence of a severe economic crises, such as the current one.…”
Section: Literature Reviewsupporting
confidence: 92%
“…Optimism represents a psychological capital that serves as a buffer against misfortune (Youssef & Luthans, 2007 ). This corresponds to the economical view of confidence related to predictability (Malovaná et al, 2021 ). As explained by Akerlof and Shiller ( 2010 ), high confidence can lead to increased optimism about the future, while low confidence leads to higher pessimism.…”
Section: Subjective Well-being Emotions and Consumers´ Consumption Ex...mentioning
confidence: 62%
“…As suggested by Ou et al ( 2014 ) or Hampson et al ( 2020 ), a distinction between the national consumer confidence (i.e., an individual’s perception about the recent and future macroeconomic climate), and personal consumer confidence (an individual’s perception about changes in their recent and future personal financial situation) improves understanding of the index. Vanlaer et al ( 2020 ) and Malovaná et al ( 2021 ) consider the personal consumer confidence more important than the national consumer confidence in determining household savings decisions.…”
Section: Consumer Confidence and Its Measurementmentioning
confidence: 99%
“…While the inclusion of "just" working papers might be frown upon, we need to keep in mind that in the central banking industry, working papers are one of the main communications tools. As such, they go through a rigorous peer-reviewing process, much like journal articles (Malovaná et al, 2020). During the screening process, we searched for working paper (journal) version for each journal article (working paper) and assessed whether and how these two versions differ (see Table 1).…”
Section: Paper Selection Proceduresmentioning
confidence: 99%